Competitiveness of Bali Province’s Cocoa Exports in the International Market - Beri Artana, I Kadek Pandi; Antara, Made; Widhianthini, Widhianthini (JURNAL MANAJEMEN AGRIBISNIS, 2024)
International trade greatly influences a country's economic growth. If a country exports more than it imports, that country's national income will increase, thus having a positive effect on economic growth. Indonesia has various products that are traded on the international market, one of which is cocoa produced by Bali Province. This research aims to analyze the competitiveness of Bali Province's cocoa exports in the international market along with the factors that influence the cocoa commodity exports. This research is quantitative descriptive research with the data used is annual data on the value of Bali Province cocoa exports for a period of 12 years from 2010 to 2021. The data collection technique used in this research is a literature study in the relevant agency ( Disperindag Bali Province). Based on data analysis, it was found that Bali Province's cocoa exports in the period 2010 - 2021 did not have a comparative advantage as shown by the RCA analysis value of 0.54. Meanwhile, if we look at the competitive advantage based on the EPD analysis value, it is found that on average the Bali Province cocoa commodity is in a falling star position, which means it has a competitive advantage but low competitiveness. The export value of Bali Province's cocoa commodities is significantly influenced by the amount of cocoa production, the USD exchange rate, and inflation. Meanwhile, the international price of cocoa has not had a significant effect on the value of Bali Province's cocoa commodity exports.